SOSIALISASI BIDANG HUKUM DENGAN TEMA SEMINAR MEMBANGUN KESADARAN KRITIS TERHADAP PELECEHAN SEKSUAL - Juhandi Juhandi; Hafidz Hanafiah; Mistia Mistia; Namira Melliyani K.; Dine Novianti; Zakia Khaulania; Sonya Gabriel; Sela Vinalia (Yayasan Education and Social Center, 2022)
Sexual harassment is any unwanted sexual act, a request to perform a sexual act, an oral or physical act or a gesture of a sexual nature or any other behavior of a sexual nature that makes a person feel offended, humiliated and or intimidated, thus creating an environment that is intimidating, hostile or disrespectful. The core definition of sexual harassment is something undesirable. In the following PKM assistance related to the legal field where a socialization seminar on sexual harassment was conducted. This seminar was held in Bojong Village, Bojong District, Pandeglang Regency, which was conducted by KKM Group 61 of Bina Bangsa University in 2022. This seminar was attended by invitees, the surrounding community, and village officials in the Bojong Village environment. The purpose of legal socialization with the theme of sexual harassment aims to find out if residents in the neighborhood experience unwanted things. Moreover, the Bojong Village area has a number of poverty and unemployment that can lead to criminal matters. As a result of the conclusion of the seminar, participants who attended were able to find out what things should be done if this happened, then what laws related to the incident on the victim and the perpetrator, as well as how to reduce the trauma effect of the victim of sexual abuse